Strategi Efektif Pembelajaran Seni Musik Untuk Siswa Kelas IV SDN 10 Kabupaten Buton Tengah - Ridwan Ardi (Jurnal Sultra Elementary School, 2026)
Music learning in elementary schools plays a crucial role in developing students' creativity, self-confidence, and social skills. However, in practice, music learning often receives little attention and is still dominated by lecture methods, resulting in less active student engagement. This study aims to describe effective music learning strategies for fourth-grade students at SDN 10, Central Buton Regency, and their impact on student engagement, creativity, and learning outcomes. This study used a qualitative approach with a descriptive approach. The subjects were arts and culture teachers and fourth-grade students. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation of sources and techniques. The results showed that teachers implemented learning strategies that emphasized demonstrations, hands-on practice, and group work. The learning media used were simple rhythmic musical instruments made from recycled materials. This strategy made students more active, enthusiastic, confident in performing, and able to work collaboratively in groups. Interviews with teachers and students revealed an increase in student interest in learning, self-confidence, and engagement in music learning. It was concluded that contextual, varied, and practice-based music arts learning strategies can holistically improve the quality of students' learning processes and outcomes. Music arts learning not only develops musical skills but also shapes the character, creativity, and social attitudes of elementary school students.